Interkoneksi Sains dalam Pembentukan Karakter Ilmiah Peserta Didik di Madrasah - fiteriani, ida; Baharudin, Baharudin (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
Idea about integration and interconnection of science and the Qur'an is not a new phenomenon in the treasury of Islamic sciences epistemology, because the grand theme of the Qur'an has a transformative and responsive function in answering the dynamics of today's nature problem which requires solving by a saintific-religious approach. In a more specific context to teach science to elementary school students (MI), many urgency benefits for the formation of religious and scientific character of children. Learning science that is designed by integrating and interconnecting science and the Qur'an can be a vehicle laying the groundwork to provide an indept understanding of the connection of the existence of this universe with the Being Substance of the Creator of the universe. When this provision is deeply rooted and forms a belief, and continues until the adult child, the character always "thirsty" towards the science will be transformed into his personality. Fiqur students like this is highly expected, because it can realize the ideals of the creation of scholars Muslim who have the breadth of science, skilled experimenting science, and have religious spiritual depth. The quality of human resources such as this can be the next generation of the nation that is able to contribute positively to the development of the nation and state, especially for the Indonesian nation that philosophizes Pancasila and the Constitution with the main principle on belief in God Almighty